(untitled) (inOpera Esercizi di lettura su testi contemporanei, 2024)
The essay offers a systematic commentary on the lyrics of Fabrizio De André’s song Don Raffaè (1990). Despite its ironic tone and seemingly tone, the song delivers a scathing social critique through a dense network of cultural references and allusions to contemporary events. By employing an original linguistic pastiche that blends “macaronic” Italian with Neapolitan dialect, the song presents itself as an entertaining and light satire that nevertheless addresses some of the most pressing issues of Italy at the time (and still today), such as the relationship between the state and organized crime, prison conditions, economic crises, and unemployment.